Character Education Management in Improving Education Quality in State Senior High School - Aini, Mulatul; Fitria, Rahmi (Journal of Islamic Education Students (JIES), 2021)
This study aims to identify and explain the management of character education in terms of planning, organizing, implementing, and monitoring in improving the quality of education in State Senior High Schools (SMAN). This research was descriptive qualitative. Sources of data in this study were principals, vice principals, and teachers. Data collection techniques were observation, interviews, and documentation, while data analysis techniques included data reduction, data display, and conclusion drawing and verification. Based on data analysis, it was found that character education management is started from planning studentsÔÇÖ character education by determining the goals, constructing programs or school activities, and integrating character values. Furthermore, the organization of character education is carried out by dividing the tasks and the person in charge of the activity or program. Next, the implementation of character education is through the integration of character values in all subjects, in the school daily activities, in school programs, as well as building communication and cooperation between schools and parents of students. Lastly, character education is done through supervision consists of observing studentsÔÇÖ behavior and scoring mentioned in studentsÔÇÖ discipline book.